NATURAL AND SUPERNATURAL IN WASHINGTON IRVING’S THE LEGEND OF SLEEPY HOLLOW AND RIP VAN WINKLE - Yonatan Christmastianto; Rr. Arielia Yustisiana (Humaniora Scientia, 2018)
The research aimed to discuss the natural and supernatural symbolism in WashingtonIrving‟s The Legend of Sleepy Hollow and Rip Van Winkle. The objectives of the researchwere to describe what the meanings of natural and supernatural symbolism were. Afterdescribed the meaning, the symbols in the stories would be related to the main characters.The theories that are used in this study were symbolism to find the meaning of natural andsupernatural symbolism in both stories. The gothic theory was to support the symbolismtheory related to supernatural symbolism. The theory of setting also supported the theory ofsymbolism. The technique of data collecting was library research, while the method of thisresearch was descriptive. There were two approaches used in the study. They werepsychological and structural approach. The result of the research showed that supernaturalaspect had an impact to people who experienced it. The first story told about IchabodCrane, he was good teacher from big city. He taught in Sleepy Hollow because of his duty.He had interest in horror story. But the urban legend of Sleepy Hollow made him leave thevillage. The second story was about Rip Van Winkle who disappeared for almost twentyyears. He had been sleeping for that time after encountered with the ghost of Hudson crew.His experienced then became a story among travellers in his village.  Keywords: Symbolism, Supernatural, Gothic.